2020
DOI: 10.5812/ijcm.100535
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Breast Cancer screening: Application of Protection Motivation Theory

Abstract: Background: Breast cancer is a major public health problem in both developed and developing countries. The mortality rates of this disease are due to the lack of awareness about screening methods and late detection of breast cancer, which is high in Iran. Objectives: The aim of this study was to determine breast self-examination (BSE) behaviors applying protection motivation theory (PMT). Methods: In this cross-sectional study, the multi-stage cluster sampling method was used to 410 women aged 40 -65 years old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 45 publications
5
6
0
Order By: Relevance
“…The findings of this study showed that self-efficacy was positively associated with screening intention. Similar to our results, in other studies, women with higher self-efficacy were more likely to perform screening regularly [ 36 , 37 , 43 , 44 ]. A meta-analysis of the PMT literature also identified that self-efficacy plays the strongest role in predicting intention [ 41 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings of this study showed that self-efficacy was positively associated with screening intention. Similar to our results, in other studies, women with higher self-efficacy were more likely to perform screening regularly [ 36 , 37 , 43 , 44 ]. A meta-analysis of the PMT literature also identified that self-efficacy plays the strongest role in predicting intention [ 41 ].…”
Section: Discussionsupporting
confidence: 92%
“…Numerous studies have been conducted to investigate the factors that may affect women’s participation in breast screening [ 17 , 33 , 34 ], but there remains relatively limited research on this topic in China, especially studies based on PMT. Previous studies in Iran have identified the importance of several PMT subcontracts in predicting breast cancer screening [ 35 , 36 , 37 ]. In these studies, increased self-efficacy, response efficacy, and perceived severity were found to be significantly associated with breast cancer screening behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the most important source of information about breast cancer screening was health staff, because the scope of primary health services and the completeness and comprehensiveness of primary health care, including health education. which is consistent with the study of Ghofranipour et al [ 19 ]. this study, approximately 25% of people performed behaviors related to breast cancer screening (breast self-examination, clinical examination or examination by physician/midwife and mammography), which is consistent with a study by Ghofranipour et al [ 16 ] and the study by Ager B et al [ 29 ].…”
Section: Discussionsupporting
confidence: 94%
“…In our example, women’s knowledge of breast cancer was low, leading to late visits to health centers. In our study, 45.6% of people had poor knowledge about breast cancer and half of the people performed breast self-examination, which is consistent with the study of Ghofranipour et al [ 19 ]. According to the World Health Organization, 55.7% of women worldwide have poor knowledge about breast cancer [ 23 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation